Qualitative Approach in Exploring Factors for Business Performance (BP) among Small Middle Enterprises (SMEs) from Information Technology Sector (ITS) in Guangzhou City of China - Liu, Chao; Chen, Dr. Yong See; Lou, Song (Transactions on Economics, Business and Management Research, 2023)
Purpose – This study explores the factors of each variables’ relationship [Top Management Support (TOP) and Competitive Pressure (CP), Electronic Commerce Adoption (ECA) and DV: Business Performance (BP)] by the collection of qualitative method based on the research framework that after it is tested followed by hypothesis question. Design/methodology/approach – The collection of qualitative method in semi-interview of 12 respondents with multiple background from Human Resource Management Department (HRMD) can be utilized, exploring the factors of each variables’ relationship by use of MAXQA2022. Findings – The presentation of qualitative approach from selected 12 respondents by semi-interview also can find out the factors of each variables’ relationship. Research limitations/implications – The qualitative method for exploring and tested each variables’ relationship in Key Successful Factors (KSFs) for implementing Electronic Commerce Adoption (ECA). The research background and research data are limited to Small Middle-sizes Enterprises (SMEs) and employees from Information Technology sectors in Guangzhou City of China. Originality/value – By studying the relationship and factors between IVs (TOP and CP), MV: ECA, and DV: BP, this paper will help to better understand how TOP and CP affect BP, and how ECA mediate the relationship between IVs: (TOP and CP) and DV: BP. With the increasing market competition and rising labor costs in China, improving and utilizing ECA for enterprises may be an important means to cope with future competition.